2018
DOI: 10.1038/s41588-018-0130-z
|View full text |Cite
|
Sign up to set email alerts
|

An interactome perturbation framework prioritizes damaging missense mutations for developmental disorders

Abstract: Identifying disease-associated missense mutations remains a challenge, especially in large-scale sequencing studies. Here we establish an experimentally and computationally integrated approach to investigate the functional impact of missense mutations in the context of the human interactome network and test our approach by analyzing ~2,000 de novo missense mutations found in autism subjects and their unaffected siblings. Interaction-disrupting de novo missense mutations are more common in autism probands, prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 71 publications
3
73
1
Order By: Relevance
“…Akin to the biologically impactful phosphorylation events in our dataset, impactful mutations exist amidst many less meaningful polymorphisms [45][46][47] . Recent efforts to identify the key mutations that underpin human disease phenotypes have utilized the expanding collection of protein structural information [48][49][50][51] , with the logic being that mutations that occur at or near the interfaces where proteins interact will have a higher likelihood of impacting protein function. Building on this logic, here we streamlined the identification of the functional phosphosites by identifying those located at or near proteininteraction interfaces (Fig.…”
Section: D Phosphoproteome Analysis Provides Insights Into Function mentioning
confidence: 99%
“…Akin to the biologically impactful phosphorylation events in our dataset, impactful mutations exist amidst many less meaningful polymorphisms [45][46][47] . Recent efforts to identify the key mutations that underpin human disease phenotypes have utilized the expanding collection of protein structural information [48][49][50][51] , with the logic being that mutations that occur at or near the interfaces where proteins interact will have a higher likelihood of impacting protein function. Building on this logic, here we streamlined the identification of the functional phosphosites by identifying those located at or near proteininteraction interfaces (Fig.…”
Section: D Phosphoproteome Analysis Provides Insights Into Function mentioning
confidence: 99%
“…Yu and coworkers show that whether a mutation falls in known or predicted protein-protein interaction interfaces is related to the likelihood to disrupt these interactions, and mostly these mutations are found on the interfaces of hub proteins [42]. Overall, they suggest that network topology should be considered when interpreting the impact of mutations.…”
Section: Resultsmentioning
confidence: 99%
“…One promising route to decipher this complexity is from the view that the cell is a network of interacting biomolecules where proteins carry out diverse functions by interacting with other proteins. We have previously demonstrated that one key feature in understanding the functional impact of mutations is whether they fall in the binding interfaces that mediate interactions with other proteins and critically, which specific interactions they mediate 21,22 . While studies of known disease mutations have already reported a strong association with protein interaction interfaces 23,24 , application of this feature has been largely limited by low coverage of structural information on interacting proteins; co-crystal structures and homology models together cover merely ~6% of all known human interactions 25 .…”
Section: Introductionmentioning
confidence: 99%